2010
DOI: 10.1002/jbm.a.32908
|View full text |Cite
|
Sign up to set email alerts
|

Keratin–hydroxyapatite composites: Biocompatibility, osseointegration, and physical properties in an ovine model

Abstract: Reconstituted keratin has shown promise as an orthopaedic biomaterial. This in vivo study investigates the biological response of composite materials prepared from reconstituted keratin containing a high content of hydroxyapatite (HA) (40 wt % HA), implanted for up to 18 weeks in the long bones of sheep. Keratin-HA composites were compared with a commercially available polylactic acid (PLA) HA composite (BIO RCI HA®, Smith and Nephew). Porous keratin-HA materials displayed excellent biocompatibility and osseoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…Further investigation into keratin hydrogel hemostatic mechanisms revealed direct acceleration of the coagulation cascade, but a specific activation mechanism has not been specified leaving safety concerns . Keratin hydrogels are expected to be biocompatible and biodegradable through macrophage phagocytosis . However, neither has been reported for hemostatic application, and degradation timescales are not well characterized.…”
Section: Biologically Derived Materialsmentioning
confidence: 99%
“…Further investigation into keratin hydrogel hemostatic mechanisms revealed direct acceleration of the coagulation cascade, but a specific activation mechanism has not been specified leaving safety concerns . Keratin hydrogels are expected to be biocompatible and biodegradable through macrophage phagocytosis . However, neither has been reported for hemostatic application, and degradation timescales are not well characterized.…”
Section: Biologically Derived Materialsmentioning
confidence: 99%
“…Keratin‐based scaffolds have been developed for bone tissue engineering (Dias et al . ,b, Kelly et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have investigated the in vivo properties of reconstituted keratin as an orthopaedic bone graft substitute . An initial in vivo study of the mass and physical strength of keratin bars in vivo (rat model) demonstrated the potential for keratin as a nonload‐bearing bone graft substitute .…”
Section: Introductionmentioning
confidence: 99%
“…Further in vivo investigations of keratin + 4% HA composites demonstrated the promising performance of porous materials, which showed excellent biocompatibility and osseointegration, with full integration into bone by 12 weeks. Microindentation showed that porous keratin–HA implants were initially soft but became stiffer as new bone penetrated the implant from 4 weeks onward …”
Section: Introductionmentioning
confidence: 99%